The Influence of combination Tithonia diversifolia compost and chicken manure with SP-36 fertilizer to P uptake and growth of maize on ultisol soil from labuhan batu selatan - Mohd Fadli Lubis; Fauzi Fauzi; Mohd Madjid Damanik (Universitas Sumatera Utara, 2018)
The aim of this research is to know the influence of a combination of T. diversifolia compost and chicken manure with SP-36 fertilizer on P Uptake and Corn Plant Growth (Zea mays L.) on Ultisol Soil Labuhan Batu Selatan. This study used Factorial Randomized Block Design (RAK) with 2 treatment factors and 3 replications. The first factor is organic material (B) consisting of 0% Organic Material (B0), 100% T. diversifolia (B1), 75% T. diversifolia + 25% Chicken manure (B2), 50% T. diversifolia + 50 % Chicken manure (B3), 25% T. diversifolia + 75% Chicken manure (B4), 100% Chicken manure(B5). The second factor is SP-36 (P) fertilizer consisting of 0 kg P2O5 / ha (P0), 50 kg P2O5 / ha (P1), 100 kg P2O5 / ha (P2), 150 kg P2O5 / ha (P3). The results of this study indicate that the application of organic matter has significant effect on P uptake, crown dry weight and root dry weight. Application of SP-36 fertilizer had significant effect on dry root weight and dry weight of canopy. The combination of oganic material with SP-36 fertilizer had significant effect on Plant P Uptake, root dry weight and dry weight of crown.Mohd Keyword : Chicken manure, SP-36 fertilizer, Tithonia diversifolia, Ultisol